Women in prison: Investigating trajectories of institutional female misconduct. (September 2017) - Reidy, Thomas J.; Cihan, Abdullah; Sorensen, Jon R.
Abstract: This study is the first to investigate the progression of serious disciplinary infractions among an imprisoned female sample. Findings from a trajectory analysis over a three-year time span revealed a three-class model with stable-limited, early-onset, and delayed-onset groups, clearly highlighting the heterogeneous nature of the female inmate population. After the classification of groups, a multinomial logistic regression was relied on to identify predictors of group membership relative to a group of "innocents" who had not committed any serious disciplinary infraction during the study period. Results from a multivariate analysis indicate that expected associations among predictors, such as age and mental health need, and disciplinary violations generally held for the rule-violating classes, especially the stable-limited group, which makes up the bulk of rule violators. These patterns and correlates are consistent with those identified in previous studies examining male inmates and pooled samples of male and female inmates.